Answer: x = − 2 and y = 1
Explanation:
Solve for the first variable in one of the equations, then substitute the result into the other equation.
/| y-x-3 = 0| y-(2*x)-5 = 0
We try to solve the equation: y-x-3 = 0
y-x-3 = 0 // + -x-3
y = -(-x-3)
y = x+3
We insert the solution into one of the initial equations of our system of equations
We get a system of equations:
/| x-(2*x)-5+3 = 0| y = x+3
-x-2 = 0 // + 2
-x = 2 // * -1
x = -2
We insert the solution into one of the initial equations of our system of equations
For y = x+3:
y = 3-2
y = 1
We get a system of equations:
/| y = 1| x = -2